Penggunaan Media Pohon Akar Pangkat Tiga (Pakar Pati) untuk Meningkatkan Kemampuan Berpikir Kritis pada Pembelajaran Matematika - Subiarto, Subiarto (Jurnal Didaktika Pendidikan Dasar, 2021)
The research objective was to improve critical thinking skills and mathematics learning outcomes through the use of Pakar Pati (Pohon Akar Pangkat Tiga) media of fifth grade students of SD Negeri 1 Kendaga. The research subjects in the study were 25 fifth grade students at SD Negeri 1 Kendaga. The method used in this research was classroom action research, by performing two actions in two cycles. Each cycle had four stages of activity, namely planning, implementation, observation and reflection. The results of this study indicated that the use of cube root tree media (Pakar Pati) can improve critical thinking skills in learning mathematics for fifth grade students of SD Negeri 1 Kendaga. Students’ ability to formulate problems, collect data, analyze, ask and answer questions, make observations and provide conclusions increases. Learning outcomes increased in the ability to solve problems and understand the cube root material.